2021
DOI: 10.1002/jbt.22734
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CRNDE functions as a diagnostic and prognostic biomarker in osteosarcoma, as well as promotes its progression via inhibition of miR‐335‐3p

Abstract: Background This study was performed to evaluate the diagnostic and prognostic value, as well as the role of long‐chain noncoding RNA (lncRNA) colorectal neoplasia differentially expressed (CRNDE) in osteosarcoma (OS). Materials and Methods A quantitative real‐time polymerase chain reaction assay was to determine lncRNA CRNDE and microRNA‐335‐3p (miR‐335‐3p) expressions. The Kaplan–Meier analysis was to analyze the relationship between lncRNA CRNDE expression and survival in patients with OS. Receiver operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…[ 10,11,29 ] lncRNAs are not only the vital early diagnostic and prognostic markers but are also the important target of the target gene therapy for OS. [ 12,30 ] LINC01410, a newly discovered lncRNA, exerted a vital part in enhancing the development of colon cancer, GC, PTC, cervical cancer, cholangiocarcinoma, and neuroblastoma by regulating cell proliferation, invasion, and migration. [ 15–20 ] Our results indicated that the LINC01410 level markedly elevated within OS cells and tissues, which indicated that LINC01410 upregulation within OS was possibly associated with OS development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10,11,29 ] lncRNAs are not only the vital early diagnostic and prognostic markers but are also the important target of the target gene therapy for OS. [ 12,30 ] LINC01410, a newly discovered lncRNA, exerted a vital part in enhancing the development of colon cancer, GC, PTC, cervical cancer, cholangiocarcinoma, and neuroblastoma by regulating cell proliferation, invasion, and migration. [ 15–20 ] Our results indicated that the LINC01410 level markedly elevated within OS cells and tissues, which indicated that LINC01410 upregulation within OS was possibly associated with OS development.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6–9 ] Numerous lncRNAs are found to participate in OS development such as ANRIL, APTR, CRNDE, HOTTIP, and LINC01410. [ 10–14 ] LINC01410, was reported to promote the tumorigenesis of colon cancer, gastric cancer (GC), papillary thyroid carcinoma (PTC), cervical cancer, cholangiocarcinoma, and neuroblastoma. [ 15–20 ] Our research group also demonstrated that LINC01410 functions as an oncogene in OS cells.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA CRNDE as a regulate gene often plays important function in cancer cells proliferation and matastasis [16]. Previous research have reported that lncRNA CRNDE was dysregulated in bladder cancer [17], renal cell carcinoma[18], gastric cancer, breast cancer and osteosarcoma [19]. By analyzed CRC tissue specimens with microarray and RT-PCR assays, LD.…”
Section: Discussionmentioning
confidence: 99%
“…As a class of non-coding RNA, miRNAs are short endogenous RNAs that are 22-25 nucleotides in length (17,18). A large number of miRNAs have been reported to participate in OS progression, including miR-873, miR-9, miR-708-5p, miR-183 and miR-17-5p (19)(20)(21)(22)(23).…”
Section: Circ-lrp6 Contributes To Osteosarcoma Progression By Regulat...mentioning
confidence: 99%